The prevalence of burnout and coping strategies among Palestinian health professionals: a cross sectional study - Ahmead, Muna; El Sharif, Nuha; Alwawi, Abdallah; Hemeid, Asma; Ziqan, Motasem (Frontiers in Public Health, 2024)
IntroductionDuring times of conflict, healthcare personnel face a heightened vulnerability to experiencing psychological problems such as burnout. The impact of conflict or wars on mental health professionals in Palestine and their strategies for managing these problems are currently not recognized. This study sought to assess the prevalence of burnout symptoms and coping strategies among healthcare workers in Palestine, in the context of the ongoing conflict and political violence.MethodsThe study utilized a cross-sectional research design. Self-reported questionnaires, including the shortened version (9 items) of The Maslach Burnout Questionnaire and Brief COPE scales, were used to gather data. The relationship between the research variables and burn symptoms was investigated using Chi-squared test, Student’s t-test, Mann–Whitney, and Analysis of variance and multi-regression.ResultsA total of 713 participants were recruited. The prevalence rates were as follows: burnout—(72.9%), emotional exhaustion (44.2%), depersonalization (9.8%), and low personal accomplishment (72.2%). The multivariate analysis found that those who worked more than 16 h per day and those who had 1–15 years of job experience were more likely to had emotional exhaustion. Active coping, substance use, informational support, and emotional support all reduced the likelihood of burnout while behavioral disengagement and self-blame increased the possibility of experiencing burnout. Finally, substance use decreased emotional exhaustion, increased depersonalization and enhanced personal accomplishment.ConclusionThe findings revealed a high prevalence of burnout among health professionals during wartime and political violence. As a result, health professionals are vulnerable to mental problems during political violence and they need immediate assistance in enhancing their mental wellbeing through psychological support, and comprehensive training in stress management.